Effectiveness of psychoeducation intervention on subjective well being and self compassion of individuals with mental disabilities - Duran, Songül; Barlas, Gül Ünsal (International Journal of Research in Medical Sciences, 2016)
Background: Our study aimed to evaluate the effects of psychoeducation on subjective well-being and self compassion given to parents of individuals with mental disabilities. Methods: We conducted our study with 66 parents (33 in control and 33 study groups) all of whom has children with mental disabilities attending to Special Education and Rehabilitation Center and Special Education-Technical School and Vocational Training Centres, Ministry of Education, Bitlis. We utilized pretest-posttest design to examine efficacy of psychoeducation programme on both control and study groups. Subjective Well-being and Self Compassion Scales were used to obtain data from control and study groups. Results: We identified significant increase in parents’ subjective well-being and self compassion levels after eight session of psychoeducation (p<0.05). Conclusions: As a result, we believe there is very few intervention practices directed to parents of children with mental disabilities and that these practices should be enhanced.